A bigger splash - Gowers, Patrick 1936-2014 (BFI, 2012)
"Auf dokumentarischer Basis werden Situationen aus dem Leben des homosexuellen Malers David Hockney geschildert. In zurückhaltender Weise verbindet der Film Hockneys Zwiespalt zwischen seiner Außenwelt und sich selbst zu einer subtilen Studie. Auch dank der ausgezeichneten Kameraarbeit ein eigenwilliges und faszinierendes Künstlerporträt." [filmdienst.de]
Original: Großbritannien 1973
Bildformat 1.85:1
Special features: presented in both High Definition and Standard Definition ; "Love's Presentation" (James Scott, 1966, 25 mins): short film capturing the creation of Hockney's "Cavafy Etchings", narrated by the artist ; "Portrait of David Hockney" (David Pearce, 1972, 13 mins): Hockney seen relaxing at his home with Peter Schlesinger, and at work on his celebrated painting "Mr and Mrs Clark and Percy" ; original theatrical trailer ; interview with Jack Hazan (Adam Roberts, 2006, 28 mins, DVD only) ; fully illustrated booklet with essays by John Wyver, Michael brooke and William Fowler as well as Jach Hazan's production stills and Philip French's original review
Keywords: Schlesinger, Peter -- 1948-; Hockney, David -- 1937-; Geschichte 1970-1973; Trennung